ANALISIS DAYA TAMPUNG BEBAN PENCEMARAN AIR SUNGAI MALAS DI KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Riduansyah; Junaidi (Jurnal Pertanian Agros, 2026)
The water quality of the Malas River, a tributary of the Kapuas River, tends to decline due to human activities such as plantations, agriculture, and settlements. This study aims to analyze the water quality and pollution load capacity (PLC) of the Malas River in Sekadau Hilir District. This study was conducted for 8 months (April to November 2025) using the Mass Balance Method stipulated by the Decree of the Minister of Environment No. 110 of 2003. This method was chosen because of its ability to comprehensively integrate water quality, flow, and pollution source data. Water sampling was carried out using a purposive sampling technique for the analysis of TSS, BOD5, COD, and Total Nitrogen parameters. The results of the analysis of the river's water pollution load capacity showed the Pollution Load Capacity (BPM) values ​​for the TSS, BOD5, COD, and Total Nitrogen parameters. After being simulated with the planned discharge of palm oil mill wastewater (POME) from PT. Agro Plankan Lestari (APL) as a significant source of pollution found that the Malas River's water pollution load capacity has not been exceeded for all tested parameters based on Class II water quality standards (PP 22 of 2021). These results serve as the basis for considerations regarding river water utilization according to its capacity.